Characterization of dual enzyme resulted from bicistronic expression of two β-glucanases in porcine cells - Xian-wei ZHANG; Zi-cong LI; Fan-ming MENG; De-hua WANG; De-wu LIU; Xiao-yan HE; Yue SUN; Yin-shan BAI; Zhen-fang WU (Journal of Integrative Agriculture)
Many animal feed grains contain high β-glucan in the cell wall. Pigs do not secret β-glucanase to degrade the β-glucan in their feed. The indigestible β-glucan not only blocks the release of nutrients from the grain cell wall, but also increases the digesta viscosity in the gastrointestinal tract of pigs. Therefore, dietary β-glucan significantly inhibits nutrient digestion and absorption in pigs. Transgenic expression of β-glucanase in the digestive tract of pigs may offer a solution to solve this problem. In the current study, four artificial codon-optimized β-glucanases genes was prepared and expressed in porcine cells. Only pBgA and pEgx showed high activity in transfected pig kidney cells. To improve the pH range and pH stability of β-glucanase, the two β-glucanases, pBgA and pEgx, were co-expressed in pig kidney cells and salivary gland cells by Linker A3 or 2A peptide. The resulting dual enzymes of pBgA3pEg and pBg2ApEg showed significantly enlarged pH range and significantly increased pH stability, as compared to parental enzymes. These results provide useful data for future study on increasing the feed digestibility of pigs by transgenic expression of β-glucanase in their salivary glands.